Effect of Compensation And Job Satisfaction on Employee Performance at PT. Tata Logam Lestari In Jakarta Barat - Muhammad Ramdhan (Universitas Negeri Makassar, 2021)
This study aims to determine the effect of compensation and job satisfaction on employee performance at PT. Tata Logam Lestari in Jakarta Barat. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study that compensation has a significant effect on employee performance by 44.4%, hypothesis testing is obtained t count > t table or (7,100 > 1,998). Job satisfaction significantly affects employee performance by 50.6%; hypothesis testing is obtained t count > t table or (8.040 > 1.998). Compensation and job satisfaction simultaneously have a significant effect on employee performance with the regression equation Y = 6.199 + 0.359X1 + 0.500X2. The contribution of influence is 63.2%, hypothesis testing is obtained by F arithmetic > F table or (53.181 > 2.750).